Bladder dose–surface maps and urinary toxicity: Robustness with respect to motion in assessing local dose effects. Issue 3 (March 2016) - Palorini, F.; Botti, A.; Carillo, V.; Gianolini, S.; Improta, I.; Iotti, C.; Rancati, T.; Cozzarini, C.; Fiorino, C.
Highlights: Robustness of bladder absorbed dose relative to daily inter-fraction motion. Systematic (SE) and random errors (RE) of bladder dose surface maps (DSM), DVH/DSH. DSH and DVH show small population SE (<3.4 cm 2 and <8.4 cm 3 ) at the highest doses. DSM show mean SE <1 Gy and population SE and RE (<4 and <3 Gy) at the posterior base. Larger variations are present in the anterior and more cranial portion of bladder. Abstract: The purpose of this study was to quantify the impact of inter-fraction modifications of bladder during RT of prostate cancer on bladder dose surface maps (DSM). Eighteen patients treated with daily image-guided Tomotherapy and moderate hypofractionation (70–72.8 Gy at 2.5–2.6 Gy/fr in 28 fractions and full bladder) were considered. Bladder contours were delineated on co-registered daily Megavoltage CT (MVCT) by a single observer and copied on the planning CT to generate dose–volume/surface histograms (DVH/DSH) and bladder DSMs. Discrepancies between planned and daily absorbed doses were analyzed through the average of individual systematic errors, the population systematic errors and the population random errors for the DVH/DSHs and DSMs. In total, 477 DVH/DSH and 472 DSM were available. DSH and DVH showed small population systematic errors of absolute surfaces (<3.4 cm 2 ) and volumes (<8.4 cm 3 ) at the highest doses. The dose to the posterior bladder base assessed on DSMs showed a mean systematic error below 1 Gy, with population systematic and random errors within 4 and 3 Gy, respectively. The region surrounding this area shows higher mean systematic errors (1–3 Gy), population systematic (8–11 Gy) and random (5–7 Gy) errors. In conclusion, DVH/DSH and DSMs are quite stable with respect to inter-fraction variations in the high-dose region, within about 2 cm from bladder base. Larger systematic variations occur in the anterior portion and cranially 2.5–3.5 cm from the base. Results suggest that dose predictors related to the high dose area (including the trigone dose) are likely to be sufficiently reliable with respect to the expected variations due to variable bladder filling.